Sexual dysfunctions and sexology: social constructions, personal meanings and medicalization of sexuality - Alarcão, Violeta Sabina Niego Perestrelo de (2016)
In contemporary constructions of sexuality, the discourses and practices of medicine and clinical psychology occupy a primary role. They contribute to the origin of new normative approaches to sexuality, focused on the issue of good sexual functioning. However, despite the growing attention that sexuality is receiving, the study of the social construction of sexual dysfunction remains incipient, especially in a national context. Overall, the results of this thesis, which integrates two studies with mixed methodologies, are presented in the form of four scientific publications. The first article aims to contribute to the discussion of how beliefs regarding sexuality and gender affect the categorization of sexual function as either natural or pathological. The second article provides a view of the dynamics of changing sexual behavior, showing a “model of human sexuality” consisting of four types: rigid conservative, attenuated traditional, adaptive progressive, and confluent transformative. The third article seeks to explore how the growing plurality of sexual scripts affects gender order through the meanings created from personal experiences in everyday life, focusing on representations of sexual problems. Finally, the fourth article analyzes how Portuguese sexologists integrate their professional role in the vast multidisciplinary field of sexual health, providing an overview of the emergence of sexology as scientia sexualis in Portugal. Preceding the four articles, there is an introduction that frames sexuality in the light of two fundamental debates: the medicalization of sexuality and growing individualization in contemporary Western societies.